유료노인요양시설(Nursing home)의 이용 결정 요인에 관한 연구 - 한승의(Seung Eui Han) (지역사회간호학회지, 2001)
Purpose : This study is to examine the characteristics of the elderly and their family caregivers. to study the main factors affecting Nursing Home utilization, and to help frame a policy about Nursing Home's demand. management and welfare facilities. Method: Data for this present study were collected via questionnaires randomly distributed to family caregivers of the over 60-year-old patients at general hospital and university hospital in Seoul. Kyung-Ki Do and In-Chon from 26 June to 20 July, 2000. Questionnaires were issued to 512 people and 479 were returned. The data was analyzed by frequency, $x^2$-test, t-test, ANOVA. factor analysis. correlation coefficients analysis and Stepwise multiple regression analysis using SPSS 9.0. Result First. Instrumental Activities of Daily Living(IADL), duration of hospitalization, sex, marital status, behavior problems, home ownership, and cognitive disorder about elderly patients affect family caregivers burden. one of need factors. Secondly, marital status. religion. health status, sex, education and age in the family caregiver predisposing factors are main factors on Nursing Home utilization. Third, in need factors, care burden. time burden, family relation burden, physical burden and mental burden have an effect on Nursing Home utilization. Finally, the model the most important factors that affect Nursing Home utilization is composed of six of eleven totally, care burden, religion, time burden, health status, marital status and education. When the family caregivers get care burden and time burden. are highly educated, have no religion, have health problems, and have no spouse, it is possibility for them to utilize Nursing Homes. Conclusion: The government should decrease a family caregivers burden and seek to find how to support Nursing Homes. Furthermore. Social support program for the family caregivers should be required. Thus, the family caregivers need consultation and need to meet to talk about their patients. how to care them, get information, which are the crucial field in advancing the research in nursing science.